The Systematic and Authenticity Of Hadith In The Book Al-Ahadits Al-Mukhtarah By Buya Mawardi Muhammad (D. 1994) - Azzahra, Annisa Fitri; Safri, Edi; Wusqa, Urwatul (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This research is motivated by Federspiel's classification of hadith literature studies up to the 20th century, where one of its categories is reflected in the presence of the book Al-Ahadits Al-Mukhtarah by Buya Mawardi Muhammad. This book is a compilation of hadith used as teaching material in Islamic schools, and it serves as important evidence of the development of hadith studies in the Nusantara, particularly in Minangkabau. The focus of this research is on the 2 (second) chapter of the book Al-Ahadits Al-Mukhtarah, which has not been extensively studied before, as it contains hadiths on the themes of deeds and morals widely used in Islamic education. However, it has not been thoroughly examined in terms of writing systematics and hadith quality. Additionally, the writing of hadiths in that book in some parts does not fully adhere to the hadith writing rules formulated by scholars, necessitating a scientific study to assess its conformity with academic standards in the hadith discipline. This research uses a qualitative approach with content analysis and takhrij al-hadits bi al-lafzhi methods to trace hadiths in the main book, focusing on 40 hadiths, which are analyzed in terms of sanad and matan and their conformity with primary sources (al-mashadir al-ashliyyah). This study found that the systematics of hadith writing in the book tends to be concise and thematic to facilitate student’s understanding. However, several editorial errors were found in both the sanad and matan aspects, which were most likely caused by the lengthy copying process, the involvement of calligraphers, and the use of references from secondary sources. In terms of quality, 72.5% of the hadiths are classified as shahih, 2.5% as hasan, and 25% as dha’if with varying degrees of weakness in the chain of narration. These findings indicate that the purpose of compiling the book emphasizes the conveyance of moral values and religious messages. Therefore, a scientific verification process is needed to improve the text and the hadith narrators so that this book remains suitable for use in the context of education and hadith studies. Penelitian ini dilatarbelakangi oleh klasifikasi Federspiel mengenai kajian literatur hadis hingga abad ke-20, di mana salah satu kategorinya tercermin dalam kehadiran kitab Al-Ahadits Al-Mukhtarah karya Buya Mawardi Muhammad. Kitab ini merupakan kompilasi hadis yang digunakan sebagai bahan ajar di sekolah-sekolah Islam, serta menjadi bukti penting berkembangnya kajian hadis di Nusantara, khususnya di Minangkabau. Fokus penelitian ini tertuju pada juz 2 dari kitab Al-Ahadits Al-Mukhtarah yang belum banyak dikaji sebelumnya, karena memuat hadis-hadis bertema amal dan akhlak yang digunakan secara luas dalam pendidikan Islam, namun belum diteliti secara mendalam dari segi sistematika penulisan dan kualitas hadis. Selain itu, penulisan hadis dalam kitab tersebut pada beberapa bagian tidak sepenuhnya mengikuti kaidah penulisan hadis yang telah dirumuskan oleh para ulama, sehingga diperlukan kajian ilmiah untuk menilai kesesuaiannya dengan standar keilmuan dalam disiplin hadis. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi dan takhrij al-hadits bi al-lafzhi untuk penelusuran hadis dalam kitab induk terhadap 40 hadis, yang dianalisis dari segi sanad dan matan serta ditelusuri kesesuaiannya dengan sumber-sumber primer (al-mashadir al-ashaliyyah). Penelitian ini menemukan bahwa sistematika penulisan hadis dalam kitab cenderung ringkas dan tematis untuk memudahkan pemahaman siswa. Namun demikian, ditemukan sejumlah kekeliruan redaksi dalam aspek sanad maupun matan, yang dapat disebabkan karena proses penyalinan yang panjang, keterlibatan penulis kaligrafi, serta penggunaan rujukan dari sumber sekunder. Dari segi kualitas, sebanyak 72,5% hadist tergolong shahih, 2,5% hasan, dan 25% dha’if dengan kelemahan yang bervariasi. Temuan ini menunjukkan bahwa tujuan penulisan kitab ini lebih menekankan pada penyampaian nilai-nilai moral dan pesan keagamaan. Sehingga, diperlukan proses verifikasi ilmiah untuk memperbaiki redaksi dan mukharrij hadis agar kitab ini tetap layak digunakan dalam konteks pendidikan dan pengkajian hadis.